Adaptation across an extreme elevational gradient in Andean leaf-eared mice, the world’s highest-dwelling mammal - Schuyler Liphardt; Naim M. Bautista; Marcial Quiroga-Carmona; Nathanael D. Herrera; L. Moritz Blumer; Juan C. Opazo; Federico G. Hoffmann; Ranim Saleem; Derek A. Somo; Francisco Del Basto Llancaqueo; Timothy J. Thurman; Timothy B. Wheeler; et al. (Science, 2026)
Andean leaf-eared mice ( Phyllotis vaccarum ) live at the highest elevations of any mammal, and they also have the broadest elevational range, from sea level to mountain summits of >6700 meters. Highland populations have evolved an enhanced thermogenic capacity in hypoxia relative to lowland conspecifics, and this improved physiological performance is associated with an increased mitochondrial respiratory capacity in skeletal muscle. Population genomic analyses identified mechanisms of hypoxia adaptation and revealed an unanticipated dimension of environmental adaptation in P. vaccarum because selection on biotransformation pathways suggests an evolved capacity to metabolize plant-derived dietary toxins. The world’s highest-dwelling mammal has adapted to habitats at both the low- and high-elevation limits of its range, and much of the elevation-related selection relates to previously unappreciated aspects of feeding ecology.